2020
DOI: 10.3390/microorganisms8091434
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Profiling and Molecular Characterization of Extended-Spectrum/Plasmid-Mediated AmpC β-Lactamase-Producing Escherichia coli Isolated from Healthy Broiler Chickens in South Korea

Abstract: We aimed to identify and characterize extended-spectrum β-lactamase (ESBL)-and/or plasmid-mediated AmpC β-lactamase (pAmpC)-producing Escherichia coli isolated from healthy broiler chickens slaughtered for human consumption in Korea. A total of 332 E. coli isolates were identified from 339 cloacal swabs in 2019. More than 90% of the isolates were resistant to multiple antimicrobials. ESBL/pAmpC-production was noted in 14% (46/332) of the isolates. Six of the CTX-M-β-lactamase-producing isolates were found to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 91 publications
(142 reference statements)
1
10
0
Order By: Relevance
“…None of the isolates harbored TEM, SHV, qnrA , qnrS , qnrC , or qnrD . We noted that some of the isolates that were sensitive by the phenotypic method harbored resistance genes, a phenomenon that has been observed by others [ 72 , 78 ]. Studies have shown that phenotypic resistance is dependent on the mode and level of gene expression [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 68%
“…None of the isolates harbored TEM, SHV, qnrA , qnrS , qnrC , or qnrD . We noted that some of the isolates that were sensitive by the phenotypic method harbored resistance genes, a phenomenon that has been observed by others [ 72 , 78 ]. Studies have shown that phenotypic resistance is dependent on the mode and level of gene expression [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, consistent with previous studies in Korea and other countries [ 28 , 37 , 38 , 39 ], we found relatively high cefoxitin and ceftiofur resistance in chicken isolates than in pig and cattle isolates. Recently, we have identified extended-spectrum β-lactamase-producing (mainly CTX-M type) Enterobacteriaceae including E. coli from food animals in Korea [ 9 , 40 , 41 ]. Cefoxitin and ceftiofur-resistant strains might contribute to the emergence of resistance to other critically important cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring antimicrobial resistance in commensal bacteria such as E. coli from food animals is vital to determine the emergence of antimicrobial resistance and its associated risk to humans. Our recent study demonstrated that more than 90% of E. coli isolated from broiler chickens in Korea exhibited resistance to several antimicrobials, including quinolones and extended-spectrum cephalosporins [ 9 ]. Several other studies have been conducted in Korea to assess the extent of antimicrobial resistance in E. coli isolated from food animals [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we successfully identified the AmpC Class C β-lactamase encoding bla CMY gene in only the early lay period of both CC and CF environments. bla CMY has been increasingly reported in chickens as a source for the spread of AmpC to both human and avian pathogenic bacteria [ 61 , 62 ]. Although bla CMY is not classified as an extended-spectrum β-lactamase, the AmpC β-lactamase is resistant to otherwise useful β-lactamase inhibitors like clavulanic acid that is often paired with antibiotics, like ceftazidime, to limit the effects of β-lactamases [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%